Determinants of life insurance purchase decisions among university students in Hanoi, Vietnam - Ngoc Huong Quynh, Pham; Tien Dung, Nguyen (Edelweiss Applied Science and Technology, 2024)
This article aims to evaluate the factors affecting the decision to buy life insurance for students in Hanoi, including the variables: awareness of life insurance value, motivations to purchase, barriers to purchase, company brand, and life insurance consultant. A quantitative survey was utilized to take the students in Hanoi, Vietnam. The study uses SPSS 20 analysis software based on 351 valid responses. The multiple regression results show that all of these factors have significant effects. Accordingly, the barrier factor has a negative impact, decreasing the ability to buy life insurance. In contrast, other factors have a positive impact, such as exceptionally high awareness of value and purchase motivation, which have the most substantial impact. Consultants and company brands also promote students’ decision to buy life insurance. Insurance companies should focus on education, improving services, and building brands to increase the ability to purchase life insurance for students. In addition, raising awareness of the value of life insurance is also necessary for student customers. The findings suggest that targeted strategies addressing these key factors can effectively boost students' adoption of life insurance in Hanoi and Vietnam.